2000
DOI: 10.1177/009164710002800205
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Perceptions of Spiritual People and Religious People

Abstract: There is great variation regarding the concepts of religiosity and spirituality in the psychology of religion literature. In an attempt to clarify these constructs in the general population, 16 college students were recruited for a task of concept mapping to elicit their perceptions of what the designations spiritual person and religious person mean. Many positive character traits were used to describe both religious and spiritual people. However, participants described spiritual people with an emphasis on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Streib et al (2009), on the basis of extensive empirical research, observe that across cultural boundaries and religious traditions, people may describe themselves as ''equally religious and spiritual, more religious than spiritual, more spiritual than religious,'' or ''neither religious nor spiritual,'' and that this may shift according to personal history and socialization, critical life events, and important developmental transitions interacting with periods in the life cycle. The same authors observe that most respondents described themselves as religious and spiritual, in keeping with the findings of Zinnbauer et al (1997), Cook et al (2000), Shahabi et al (2002), and Corrigan et al (2003). Together, these researchers observe that despite the contrasting positions of religion and spirituality in a small minority of subjects, and the use of ''spiritual'' as an explicitly anti-religious term in an even smaller subgroup of this minority, spiritual growth is viewed as something that can and does occur in what most subjects perceive to be the highly supportive framework of religion.…”
Section: Religious Development and Spiritual Development: Defining Thsupporting
confidence: 76%
“…Streib et al (2009), on the basis of extensive empirical research, observe that across cultural boundaries and religious traditions, people may describe themselves as ''equally religious and spiritual, more religious than spiritual, more spiritual than religious,'' or ''neither religious nor spiritual,'' and that this may shift according to personal history and socialization, critical life events, and important developmental transitions interacting with periods in the life cycle. The same authors observe that most respondents described themselves as religious and spiritual, in keeping with the findings of Zinnbauer et al (1997), Cook et al (2000), Shahabi et al (2002), and Corrigan et al (2003). Together, these researchers observe that despite the contrasting positions of religion and spirituality in a small minority of subjects, and the use of ''spiritual'' as an explicitly anti-religious term in an even smaller subgroup of this minority, spiritual growth is viewed as something that can and does occur in what most subjects perceive to be the highly supportive framework of religion.…”
Section: Religious Development and Spiritual Development: Defining Thsupporting
confidence: 76%
“…Notably, most of the respondents in this study identified themselves as both spiritual and religious (74%); in contrast, 19% identified themselves as spiritual but not religious, and 4% labeled themselves as religious but not spiritual. Whereas certain subgroups such as mental health professionals, New Agers, and college students were more likely than others to identify themselves as spiritual but not religious, this study indicated that most people view the terms as distinct and view themselves as both religious and spiritual (see also Cook, Borman, Moore, & Kunkel, 1997).…”
Section: Criticismsmentioning
confidence: 69%
“…The process of survey development began with an exploration of various definitions of "spirituality" proposed by scholars in business, education, health, psychology, sociology, and other fields (see, for example, Ashmos & Duchon, 2000;Baker, 2003;Burack, 1999;Cannister, 1998;Cook et al, 2000;Dehler & Welsh, 1997;Dyson et al 1997;Gibbons, 2000;Hayes, 1984;Hill & Pargament, 1993;Hodge, 2001;Krahnke & Hoffman, 2002;Love & Talbot, 1999;Maher & Hunt, 1993;Pargament, 1999;and Rose, 2001). Because a number of psychologists and measurement specialists during the past decade have also attempted to develop measures of "spirituality" and "religiousness," this critical body of work was reviewed as well.…”
Section: Development Of the College Students' Beliefs And Values (Csbmentioning
confidence: 99%